Recent Developments of Cathode Materials for Thermal Batteries - Li, Renyi; Guo, Wei; Qian, Yumin (Frontiers in Chemistry, 2022)
Big progress has been made in batteries based on intercalation mechanism in the last twenty years, but limited capacity in batteries hinders their further increase in energy density. The demanding for more energy intensity makes the research communities turn into the conversion-type battery. Thermal batteries are a special kind of conversion-type battery, which are thermally activated primary batteries composed mainly of cathode, anode, separator (electrolyte) and heating mass. Such kinds of battery employ an internal pyrotechnic source to make the battery stack reach its operating temperature. Thermal batteries have a long history of research and usage in military fields because of their high specific capacity, high specific energy, high thermal stability, long shelf lives and fast activation. These experiences and knowledge are of vital importance for the development of conversion-type battery. This review provides a comprehensive account of recent studies on cathode materials. The paper covers the preparation, characterization of various cathode materials, and the performance test of thermal batteries. These advances have significant implications for the development of high-performance, low cost and mass production conversion-type batteries in the near future battery research communities.